VD_FINDINFO Décision / 2015 / 520 vom 6. Juli 2015 - VD Tribunal cantonal (2015)
RÉCUSATION, DROIT D'OBTENIR UNE DÉCISION, PRINCIPE DE LA CÉLÉRITÉ, RETARD INJUSTIFIÉ | 29 al. 1 Cst., 30 al. 1 Cst., 393 al. 2 let. a CPP (CH), 56 let. f CPP (CH), 59 CPP (CH)